Heat Index Based Optimisation of Primary Process Parameters in Friction Stir Welding on Light Weight Materials. (25th September 2022) - Joseph Leon, Stephen Leon; Manikandan, N.; Santhanakrishnan, R.; Al-Khafaji, Mohsin O.; Mahmood Salman, Hayder; Anandaram, Harishchander; Malkiya Rasalin Prince, R.; Karthick, L.; Rajesh Sharma, R.
Abstract : In friction stir welding, tool shoulder diameter and its rotational speed are the major influencing parameters than others. A simple novel correlation is proposed to select the optimum range of tool shoulder diameter with respect to the chosen rotational speed and vice versa. The conditions to apply derived correlation were defined through process heat index number as the joint efficiency in the friction stir welding depends on the effective heat supply to the volume of material deformed in the stir zone. Weld speed is the key parameter through which generated heat can be regulated towards optimum heat supply to attain defect-free weld in the stir zone. Effective heat input also has obvious effect on grain growth and corresponding property eradication in the heat affected zone. The experimental study was carried out on AA2024-T3 plates to understand the effect of process heat index on the prescribed optimum range of tool shoulder and rotational speed defined in the correlation. Eventually, a novel relationship was attained between the first order process influencing parameters to deliver maximum joint efficiency.